Effects of tree mycorrhizal dominance on soil microbial community structure and microbial nutrient limitation - Xu, Yajie; Hao, Longfei; Yue, Yongjie; Gao, Runhong; Zhang, Lingze; Zhao, Kai; Zhao, Zhenghui (Frontiers in Microbiology, 2026)
IntroductionMycorrhizal fungi play a central role in nutrient cycling in forest ecosystems. The functional differences between arbuscular mycorrhizal (AM) and ectomycorrhizal (EcM) tree species significantly affect soil microbial community structure and patterns of microbial nutrient limitation, with substantial implications for ecosystem stability and biogeochemical cycling under global changes. However, the regulatory mechanisms of different dominant mycorrhizal tree species and their mixed mycorrhizal configurations on microbial nutrient limitation remain unclear.MethodsThis study investigated a typical AM tree species (Ulmus pumila) and an EcM tree species (Pinus sylvestris var. mongolica) in the southern Horqin Sandy Land. We compared rhizosphere soil nutrient status, extracellular enzyme activities, and microbial community structure among pure U. pumila stands, pure P. sylvestris var. mongolica stands, and U. pumila–P. sylvestris mixed stands.ResultsResults showed that AM pure forests exhibited extremely high C-acquiring enzyme activities but reduced soil nutrient content and microbial biomass, maintaining higher bacterial diversity. By contrast, the activities of N- and P-acquiring enzymes, soil nutrient contents, and fungal diversity in the EcM pure stands were significantly higher than those in the AM pure stands (p < 0.05). Mixed forests improved soil nutrient status through complementary mixed-mycorrhizal strategies, promoted microbial biomass accumulation, and modulated extracellular enzyme activities, thereby significantly alleviating microbial nutrient limitations. Moreover, their microbial networks exhibited greater complexity and stability than pure stands. Structural equation modeling further revealed that tree mycorrhizal dominance and microbial biomass were the primary factors alleviating microbial nutrient limitation: microbial biomass and mycorrhizal dominance showed significant negative effects on vector length (path coefficients −0.71 and 0.33, p < 0.01), whereas mycorrhizal dominance exerted a highly significant positive effect on vector angle (path coefficient 0.70, p < 0.001).DiscussionIn conclusion, mixed mycorrhizal strategies alleviate microbial nutrient limitations by enhancing soil nutrient status, microbial community structure, and extracellular enzyme activities, providing theoretical support for ecosystem restoration and sustainable development in arid regions.